Reduction of lead time for better delivery of customized cabinet product - Nur Zuadliana, Zulkifli (2016)
This study is entitled of reduction of lead time for better delivery of customized cabinet product. This research was conducted in the furniture company in Kuantan and the company is participated in this research to completethis research which is focusing on reduction of lead time for each process. The objective of the research is to identify the elements that contribute on the longer lead time of producing the customized cabinet product, to analyse which strategy that can be implement in the process to reduce the lead time and the last objective is to propose a suggestion of improvement to the process of making customized cabinet. The researcher will identify all the process that involved in the process of producing the customized cabinet in the company and will only focusing on sub process that involved the process of prepare materials, measurements, cutting, patching, making body and glue, finishing and painting and drying. The method that has been used by the researcher in order to complete this study is time study. The researcher observe the time study of each process to record the past lead time of each process in the company and the time study is structured in the table. After that, the researcher identify the causes that contributed on the longer lead time in the process and find out the factors that caused the longer lead time in order to minimizing the lead time and the root cause of each process is structured by using Ishikawa’s diagram or also called as Cause and Effect diagram. The last method is using Failure Mode and Effect Analysis (FMEA) to identify the most critical process that contribute on the longer lead time and to rank the severity (SEV), occurrence (OCC), detection (DET), and RPN. The data is collected by the observation and interviews. In addition, the strategy or suggestion of improvement is structured in the table in chapter 5. The proposals are references from literature from past researchers as a guide and additional information.